Evaluation of the Relationship between Early Troponin Clearance and Short-Term Mortality in Patients with Chronic Renal Failure. (31st January 2020) - Ozbek, Ahmet; Algın, Abdullah; Tas, Gokhan; Erdogan, Mehmet Ozgur
Abstract : Objective . In patients with CKD, cTn concentrations may be elevated in the absence of AMI, which is a predicted finding caused by chronic structural heart disease rather than acute injury. The increase in troponin level observed in noncardiac conditions provides conflicting results when predicting mortality. Low lactate clearance was associated with increased mortality. Lactate clearance is calculated as follows: (early lactate − late lactate/early lactate) ∗ 100. We aimed to investigate whether troponin clearance calculated according to this formula had an effect on short-term mortality. Methods . The study included 300 patients with chronic renal failure who had a sepsis-related organ failure assessment (SOFA) score ≥3. By taking the baseline troponin at the time of emergency presentation as reference and comparing them with the fourth-hour troponin values, troponin clearance was investigated in the evaluation of mortality among hospitalized patients with CKD within the first month after discharge. The data obtained were analyzed using the SPSS data analysis software version 20.0. Student's t -test was used for the parametric data, and the Chi-squared test for the nonparametric data. Results . Of the 300 patients evaluated, 189 patients survived (mean age 66.20 ± 14.597 years), and 111 died (mean age 74.81 ± 12.916 years). Troponin clearance was detected in 40 of the 111 patients in the mortality group and 119 of the 189 patients in the survival group. Troponin clearance was significantly more frequent in surviving patients (P = 0.0000083 ). Conclusion . Troponin clearance can be considered as a valuable leading indicator of survival, but higher levels of troponin clearance did not lead to higher survival rates.